TRACHYPENAEOPSIS MINICOYENSIS SP. NOV. (PENAETDAE, DECAPODA) FROM THE LACCADIVE SEA - Thomas, M M (Indian Journal of Fisheries, 2011)
The genus Trachypenaeopsis Burkenroad is reported for the lirst time from theIndian Region and a new species T. minicoyensis collected from Minicoy Island, LaccadiveArchipelago, is described in detail. The present species differs from other known speciesviz., T. richtersii (Miers) and T. mobillspinis (Rathbun) in the structure ot the petasma, thelycumand telson. A key to the identification of the known species of the genus is alsoprovided.